Accounting Standards Reporting in Digital Technologies: Exploring Benefits, Challenges, and Potential Risks - Abalaka James Nda; Lukman Ojedele Lawal; Sulaiman Taiwo Hassan (International Journal of Science and Society (IJSS), 2026)
The rapid advancement of digital technologies such as Artificial Intelligence (AI), machine learning, cloud computing, and big data analytics has significantly transformed accounting and financial reporting practices in the era of the Fourth Industrial Revolution. However, despite the increasing adoption of these technologies, there remains limited understanding regarding their overall benefits, risks, and implications for the accounting profession. This study aims to critically examine the impact of digital technologies on accounting standards reporting by exploring their advantages, challenges, and potential risks. The research employed a qualitative approach using a systematic literature review guided by the Technology Acceptance Model (TAM). Relevant peer-reviewed articles were collected from databases including Scopus, Web of Science, Google Scholar, and ScienceDirect, and analyzed using thematic analysis. The findings reveal that digital technologies improve accounting efficiency, enhance audit quality, reduce operational costs, support real-time financial reporting, and increase the accuracy and reliability of accounting information. Nevertheless, several challenges persist, including cybersecurity threats, data privacy concerns, inadequate digital competencies among accounting professionals, high implementation costs, and the risk of structural unemployment due to automation. The study concludes that digital transformation has become an essential component of modern accounting practices, offering substantial opportunities for improved performance while simultaneously introducing significant risks that require effective management. Therefore, accounting practitioners, educational institutions, and policymakers are encouraged to invest in digital infrastructure, cybersecurity systems, and continuous professional training. The findings provide important implications for the development of digital accounting policies, professional competency frameworks, and future research on technology-driven accounting practices.